The security measures in the era of imam Al-Hassan Bin Ali - Saif Hameed Daiyekh Al-Awadi, Ali Abed Mashali Al-Augaily, (Opción, 2019)
The aim of the study is to investigate the security measures in the era of Imam Al-Hassan Bin Ali via comparative qualitative research methods. As a result, the Omawi State has originated during this year despite the security disruption which one of its reasons was the intent of Moawiya to take over the caliphate from Imam Al-Hassan. In conclusion, the loss of consistency and unity inside the Arabic society led to the security collapse of the Islamic nation partially and the ultimate strike to the nation’s security came after the assassination of Imam Al-Hassan